Development of an IoT-Based Ship Engine Performance Monitoring System to Enhance Operational Efficiency - Sutrisno, Imam; Umasangadji, Fahmi; Ardiansyah; Almuzani, Nafi; Bashori, Achmad; Mudjiono, Urip; Priyonggo, Projek; Purwanti, Endang Pudji (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to develop an IoT-based ship engine performance monitoring system to enhance operational efficiency in marine vessels. The study introduces a real-time monitoring prototype integrating sensors, microcontrollers, and cloud-based data visualization. The variables observed include engine temperature, RPM, and fuel consumption. The methodology follows a design and implementation approach, tested on a diesel-powered training ship over a two-week observation period. Data were collected continuously and analyzed to detect performance anomalies and efficiency trends. Results show that the system improves situational awareness and enables proactive maintenance decisions. The developed system has implications for reducing fuel costs, extending engine life, and supporting digital transformation in marine engineering operations